Enhancement the Productivity of Processing Category Potato by Biochar - Roy, TS; Das, BR; Sultana, N; Chakraborty, R; Rahman, MS (Bangladesh Agronomy Journal, 2022)
The application of biochar may enhance the yield of potato for different processing categories. A field experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka-1207, during the period from November, 2020 to April, 2021 to find out the response of biochar on yield of potato for different processing categories. The experiment comprised of Potato varieties (3): V1: BARI Alu-29 (Courage), V2: BARI Alu-28 (Lady Rosetta) and V3: BARI Alu-25 (Asterix) and Biochar level (5): B0: 0 t ha-1, B1: 2.50 t ha-1, B2: 5.00 t ha-1 and B3: 7.50 t ha-1 and B4: 10 t ha-1. The study was laid out in a randomized complete block design with 3 replications. The results showed that biochar amendment could enhance the yield of processing category potato. The total yield and marketable yield of potato gradually increased with increasing biochar level. The results also revealed that the processing category potato viz., canned, chips and French fry potato yield progressively increased with advancing biochar level irrespective of varieties except dehydrated category. In case of marketable yield, BARI Alu-25 and BARI Alu-29 with biochar level 5 to 10 t ha-1performed superior than other combinations and produced 19.50 to 21.30 t ha-1which are 18.54 to 36.45% higher than without biochar. The combination of V2B4 produced maximum canned (8.10 t ha-1) and dehydrated potato (10.09t ha-1) but V3B4 made significantly highest chips (9.03 t ha-1) and French fry (5.70 t ha-1) potato, whereas, BARI Alu-29 and BARI Alu-28 did not produce any French fry category potato. However, the level of biochar of 5 to 10 t ha-1 could enhance processing category potato production. It may be concluded that potato growers may apply biochar along with recommended rate of other fertilizers for producing maximum processing category potato. Bangladesh Agron. J. 2021, 24(2): 63-72